Eficiência socioeconômica das cooperativas de crédito brasileiras - Espich, Denise (2019)
Credit unions are organizations with economic and social ends, with proven importance for society, therefore, this study aimed to analyze the efficiency of Brazilian credit cooperatives, as well as their main determinants, in the years 2016 and 2017. It is important to highlight the relevance of this study to broaden the literature on socioeconomic efficiency, which has not been discussed until now, as well as to help credit cooperatives in understanding their levels of efficiencies and the factors that can define them. In order to determine the level of efficiency of credit cooperatives, a method of stochastic data envelopment analysis (SDEA), proposed by Simar and Wilson (2000), was used, and a quantile regression was used to evaluate its environmental determinants. data. The results show that social efficiency is reached by more than 10% of credit cooperatives, but there is a great distance of this efficiency from some organizations. There has been a reduction in the efficiency level of 59% of the cooperatives analyzed from 2016 to 2017. Furthermore, the environmental factors positively associated with social efficiency are urban concentration; size, measured by assets; capital adequacy; number of service stations; savings per member and the regional effect of the South region. In a negative way by size, relative to members, and incorporations. Regarding economic efficiency, it was found that few cooperatives have achieved efficiency, but many are close to it. Also, it was verified a reduction of the economic efficiency of 2016 to 2017, of 63% of the credit cooperatives. Still, with regard to environmental factors, the urban concentration positively affects economic efficiency; size, relative to the number of members; capital adequacy, control of the regional effect of the South, Southeast, Midwest and Northeast regions; and incorporations. And negatively is the size, measured by the assets, and the number of service stations. Finally, with respect to socioeconomic efficiency, it was verified that more than 10% of the analyzed cooperatives reached the total level of efficiency. However, 69% of the cooperatives analyzed reduced their efficiency from 2016 to 2017. Furthermore, the environmental factors that affect socioeconomic efficiency were positive: urban concentration; the size, measured by the number of members; capital adequacy; savings per member; the control of the regional effect of the South and Southeast regions. And negatively were the size, in relation to the asset, and the number of service stations.